1996
DOI: 10.1016/s0014-5793(96)01299-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nucleoside diphosphate kinase activity by in vitro phosphorylation by protein kinase CK2 Differential phosphorylation of NDP kinases in HeLa cells in culture

Abstract: Although a number of nucleoside diphosphate kinases (NDPKs) have been reported to act as inhibitors of metastasis or as a transcription factor in mammals, it is not known whether these functions are linked to their enzymatic activity or how this protein is regulated. In this report, we show that in vitro protein kinase CK2 catalyzed phosphorylation of human NDPK A inhibits its enzymatic activity by inhibiting the fust step of its ping-pong mechanism of catalysis: its autophosphorylation. Upon in vlvo 32P label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…In fact, two prior studies, one in Escherichia coli (Almaula et al , 1995) and a proteome-wide phospho-mapping study in Drosophila (Zhai et al , 2008), found this serine (S120) to be a candidate for phosphorylation. In addition, in vitro assays mixing protein kinase CK2 (CK2; formerly casein kinase 2) with NDPK demonstrated that serine phosphorylation of NDPK may be a mechanism to negatively regulate its activity (Biondi et al , 1996) and indicate that the serine phosphorylation of NDPK may inhibit NDPK's phosphotransferase function (Treharne et al , 2009), which are in agreement with our results. Therefore, NDPK activity, which normally has a high turnover rate, might be partially inhibited by serine phosphorylation (Biondi et al , 1996).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, two prior studies, one in Escherichia coli (Almaula et al , 1995) and a proteome-wide phospho-mapping study in Drosophila (Zhai et al , 2008), found this serine (S120) to be a candidate for phosphorylation. In addition, in vitro assays mixing protein kinase CK2 (CK2; formerly casein kinase 2) with NDPK demonstrated that serine phosphorylation of NDPK may be a mechanism to negatively regulate its activity (Biondi et al , 1996) and indicate that the serine phosphorylation of NDPK may inhibit NDPK's phosphotransferase function (Treharne et al , 2009), which are in agreement with our results. Therefore, NDPK activity, which normally has a high turnover rate, might be partially inhibited by serine phosphorylation (Biondi et al , 1996).…”
Section: Discussionsupporting
confidence: 91%
“…14 Protein kinase CK2, formerly known as casein kinase 2, is a constitutively active 2α, 2β heterodimer, 15 and has a growing list of over 300 in vivo protein substrates and plays an essential role in almost every process in the cell. 16,17 CK2 phosphorylates NDPK in vivo, 18 and we reported recently that protein kinase CK2 interacts with the NDPK-A/ AMPK α1 substrate-channelling complex 2 under basal conditions and provided insight into the mechanism of interaction of the cytosolic NDPK-A/AMPK α1 complex with CK2, whereby the association of CK2α with NDPK-B is an NDPK-A and S122-dependent process. 19 Lactate dehydrogenase (LDH) is a tetramer composed of either M (muscle) and/or H (heart) subunits, which may combine to form five distinct LDH isozymes based on combinations of the two isoforms.…”
Section: Introductionmentioning
confidence: 91%
“…1). Interestingly, in vitro data suggest that CK2 may target NDPK (Biondi et al 1996) inhibiting NDPK function by phosphorylating S120 near the NDPK catalytic site at H118 (right panel in Fig 1). In addition, unlike the overwhelming majority of protein kinases, NDPK and CK2 can both use ATP or GTP as substrates whereas most kinases such as PKA and AMPK only use ATP.…”
Section: Protein Kinase Ck2 a Regulator Of Many Proteinsmentioning
confidence: 98%